2016
DOI: 10.1016/j.celrep.2016.08.037
|View full text |Cite
|
Sign up to set email alerts
|

A Phenotype-Driven Approach to Generate Mouse Models with Pathogenic mtDNA Mutations Causing Mitochondrial Disease

Abstract: SummaryMutations of mtDNA are an important cause of human disease, but few animal models exist. Because mammalian mitochondria cannot be transfected, the development of mice with pathogenic mtDNA mutations has been challenging, and the main strategy has therefore been to introduce mutations found in cell lines into mouse embryos. Here, we describe a phenotype-driven strategy that is based on detecting clonal expansion of pathogenic mtDNA mutations in colonic crypts of founder mice derived from heterozygous mtD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
135
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(149 citation statements)
references
References 48 publications
14
135
0
Order By: Relevance
“…The observed level of accumulation of variants present in blood should not be seen as a baseline level, caused by an absence of purifying selection. As a matter of fact, the low number of variants detected in blood samples could be due to selection that acts during life thanks to the rapid turnover of this cell type as already reported in previously published works (Larsson et al, 1990;Ciafaloni et al, 1991;Rajasimha et al, 2008;Pallotti et al, 2014;Kauppila et al, 2016). Interestingly, between PBs, the intra-individual approach indicated unequal accumulation as one thousand times more likely (BF = 9.2e −04 ), but when looking across individuals the result was inverted, and equal accumulation was five times more likely (BF = 5.03).…”
Section: Quality and Quantity Of Mtdna Variants Across Cell Typesmentioning
confidence: 85%
“…The observed level of accumulation of variants present in blood should not be seen as a baseline level, caused by an absence of purifying selection. As a matter of fact, the low number of variants detected in blood samples could be due to selection that acts during life thanks to the rapid turnover of this cell type as already reported in previously published works (Larsson et al, 1990;Ciafaloni et al, 1991;Rajasimha et al, 2008;Pallotti et al, 2014;Kauppila et al, 2016). Interestingly, between PBs, the intra-individual approach indicated unequal accumulation as one thousand times more likely (BF = 9.2e −04 ), but when looking across individuals the result was inverted, and equal accumulation was five times more likely (BF = 5.03).…”
Section: Quality and Quantity Of Mtdna Variants Across Cell Typesmentioning
confidence: 85%
“…mtDNA mutations can be introduced into mouse germ cells (Inoue et al, 2000), or they can be induced to occur as a consequence of a proofreading-deficient DNA polymerase gamma (Kauppila et al, 2016). However, the generated mouse models cannot recapitulate the heteroplasmy or tissue specificity of mtDNA disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Surf1 knockout mice are reported to suffer a loss between 30% and 50% of COX activity , whereas mtDNA mutator mice lose around 25–30% . Mice harbouring the mt‐tRNA ALA mutation show only sparse COX impairment . The NBTx assay revealed that in these mouse models, qualitative levels of formazan crystal deposition correlated with the reported mitochondrial COX deficiency (Figure ).…”
Section: Resultsmentioning
confidence: 93%